Противодействие сексуальному насилию во время вооруженных конфликтов - Toma, Mariana (Prevenirea hărțuirii: realitate și soluții legislativ, 2021)
The term „sexual violence” refers to acts of a sexual nature committed with the use of force or coercion, which can take the form of threats of violence, pressure, imprisonment, psychological violence or abuse of power against a person (man, woman, boy or girl). Coercion is also the use of a coercive environment / environment or the victim's inability to give informed consent. Such acts are rarely carried out in isolation. They are usually part of a common scenario of abuse and violence, which includes murder, child recruitment, property destruction and looting. Sexual violence can be used as a reprisal, intimidation, or as a means of torture. It can also be used systematically as a method of warfare aimed at destroying the very fabric of society. Armed conflicts and other situations of violence affect women, men, girls and boys in different ways. Some people are more at risk of sexual abuse than others. These include, inter alia, internally displaced persons, migrants, widows, women heads of households, persons deprived of their liberty, persons associated with armed forces or groups, and members of certain ethnic groups.
Keywords: violent actions; sexual violence; coercion; warning